2018
DOI: 10.1016/j.chest.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining Permissive Hypercapnia in ARDS

Abstract: Lung-protective ventilation (LPV) has become the cornerstone of management in patients with ARDS. A subset of patients is unable to tolerate LPV without significant CO elevation. In these patients, permissive hypercapnia is used. Although thought to be benign, it is becoming increasingly evident that elevated CO levels have significant physiological effects. In this narrative review, we highlight clinically relevant end-organ effects in both animal models and clinical studies. We also explore the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 85 publications
0
41
0
2
Order By: Relevance
“…Lung-protective ventilation with lower tidal volumes (6 mL/kg) is desirable but may lead to hypercapnia and acidaemia [73]. However, permissive hypercapnia may have a negative effect on the kidney through reduced renal plasma flow and increased renal vascular resistance [119]. In theory, RRT helps compensate respiratory acidosis and may remove CO 2 through additional filters included in the CRRT circuit [extracorporeal CO 2 removal (ECCO 2 R)] [96,120,121].…”
Section: Rationalementioning
confidence: 99%
“…Lung-protective ventilation with lower tidal volumes (6 mL/kg) is desirable but may lead to hypercapnia and acidaemia [73]. However, permissive hypercapnia may have a negative effect on the kidney through reduced renal plasma flow and increased renal vascular resistance [119]. In theory, RRT helps compensate respiratory acidosis and may remove CO 2 through additional filters included in the CRRT circuit [extracorporeal CO 2 removal (ECCO 2 R)] [96,120,121].…”
Section: Rationalementioning
confidence: 99%
“…37,38 Acute respiratory distress patients often attempt to increase minute ventilation, thus potentially worsening ventilator dyssynchrony, secondary to a multitude of reasons including anxiety and compensation for permissive hypercapnia. 39 While deep sedation can blunt this high respiratory drive and minute ventilation, and ventilator setting adjustments can reduce ventilator dyssynchrony, 40 complete control of the ventilator-patient interface may only be accomplished via paralysis.…”
Section: Potential Physiologic Benefitsmentioning
confidence: 99%
“…The primary endpoint was oxygenation during the 120 hours after randomization, as measured by serial P/F ratios. The authors found the cisatracurium group had a significant improvement in oxygenation over the 120-hour study time Table 2 Potential physiologic benefits and harms of neuromuscular blockade in acute respiratory distress syndrome 24,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%
“…Ventilations are always needed to correct hypoxemia [3,4] To avoid or reduce pulmonary morbidity, the low tidal volume ventilation is often applied [5,6]. The ventilation strategy will certainly result in hypercapnia, which is called "permissive hypercapnia" [7,8]. Our previous study found that hypercapnia could induce IL-1β overproduction in hypoxia-activated microglia [9].…”
Section: Introductionmentioning
confidence: 99%